Clinical and Cardiovascular Magnetic Resonance Predictors of Early and Long-Term Clinical Outcome in Acute Myocarditis - Bohbot, Yohann; Garot, Jérôme; Hovasse, Thomas; Unterseeh, Thierry; Di Lena, Chloé; Boukefoussa, Wahiba; Tawa, Chloé; Renard, Cédric; Limouzineau, Isabelle; Duhamel, Suzanne; Garot, Philippe; Tribouilloy, Christophe; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The natural history of acute myocarditis (AM) remains partially unknown and predictors of outcome are debated. We sought to assess the impact of various cardiac magnetic resonance (CMR) parameters on early and long-term prognosis in a population of patients with AM. Materials and Methods: In a bicentric longitudinal study, we included consecutive patients with a CMR-based diagnosis of AM. The primary endpoint was the occurrence of an event in the acute phase (≤15 days). Secondary endpoints were the occurrence of major adverse cardiac events (MACE) and recurrence of AM during follow-up. Results: Three hundred and eighty-eight patients were included (mean age 38.5 years, 77.3% male, mean ejection fraction [EF]:56%) of which 82% (317) presented with chest pain. CMR was performed 4±2 days after index presentation. Overall, 44 patients (11.3%) had an event at the acute phase, 41 (10.6%) presented at least one MACE during follow-up (median 7.5 years, 6.6-8.9) and 30 (7.7%) experienced a recurrence of AM. By multivariate analysis, the independent predictors of initial complications were absence of chest pain (OR[95%CI]=0.37[0.17-0.82]), presence of syncope/lypothymia (OR[95%CI]=4.13[1.55-10.98]), lower EF (OR[95%CI]=0.94[0.91-0.98] per %), myocardial extent of late gadolinium enhancement (LGE) (OR[95%CI]=1.05[1.003-1.100] per % ) and absence of edema (OR[95%CI]=0.44[0.21-0.95]). Only age (HR[95%CI]=1.021[1.001-1.041] per year) and an initial alteration of EF (HR[95%CI]=0.94[0.91-0.97] per %) were associated with MACE during follow-up. Factors independently associated with AM recurrence were myocarditis prior to the index episodes (HR[95%CI]=5.74[1.72-19.22]) and viral syndrome at the index episode (HR[95%CI]=4.21[1.91-9.28]). Conclusion: In routine consecutive patients with CMR-based diagnosis of AM, absence of edema, reduced EF, and extent of LGE were associated with early outcome. Only age and EF were associated with long-term events.